Considerações sobre o campesinato no Século XXI: graus de campesinidade e agroindustrialização na comunidade de Sítio Palmeiras, Chã Grande - Pernambuco - CAPORAL, Ladjane de Fátima Ramos (2013)
In this study, there was a need to understand and characterize the contemporary peasant through the reading of classic studies, Brazilian studies and the contemporary studies of the farm laborers. Also, an empirical research was done in a community located in Chã Grande, at the Zona da Mata Norte of Pernambuco, aiming at the identification of typologies and degrees of peasant moral order and agroindustrialization in the rural area as a mean to establish types of peasants and agroindustrial or modern producers. On the other hand, contributions were made to differentiate the farm laborers in a wide social segment that is under the family agriculture umbrella, therefore being very used in public policies and by some academic studies. Therefore, this study aimed at characterizing and identify the presence of the farm laborers in the contemporary rural world, in a way to contribute to the creation of different public policies, as in improving the knowledge of the different ways of life that assure the existence of a farm laborer, even when it was expected that the peasants had succumbed facing the modernization force imposed during the Green Revolution.